Identifikasi Organisme Pengganggu Tanaman Pada Perkebunan Kelapa Sawit (Elaeis guineensis Jacq.) di Kecamatan Rokan IV Koto Provinsi Riau - Lestari, Siti; Fransiska, Maria; Hakim, Abdul; Juliarni, Juliarni (AGRORADIX : Jurnal Ilmu Pertanian, 2025)
Oil palm (Elaeis guineensis Jacq.) is one of Indonesia's strategic plantation commodities with high economic value, both nationally and internationally. However, the success of oil palm cultivation also faces serious challenges, particularly from plant pest organism that can significantly reduce crop productivity. This study aims to observe and identify plant pest organism in oil palm plantations in Rokan IV Koto Subdistrict, Rokan Hulu District, Riau Province. The method used was descriptive-exploratory with a field survey approach conducted over various plant growth phases for a duration of three months. Samples were purposively taken from three land blocks with the highest attack intensity. The results showed that the main types of plant pest organism found included crown disease, basal stem rot (Ganoderma boninense), fruit rot, and nettle caterpillar (Setora nitens).